2006
DOI: 10.1542/peds.2005-0801
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Removable Splinting Versus Casting for Wrist Buckle Fractures in Children

Abstract: Children treated with removable splinting have better physical functioning and less difficulty with activities than those treated with a cast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
114
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(124 citation statements)
references
References 17 publications
(30 reference statements)
6
114
0
1
Order By: Relevance
“…We found that in all the children with torus fractures, cast immobilization was successful, with no displacement and no complications, so that the inclusion of additional radiographs during management or after cast removal would have had no added benefit. These results support previous studies indicating that forearm torus fractures in children may be safely treated using a wrist splint that can be removed at home by the parents [12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…We found that in all the children with torus fractures, cast immobilization was successful, with no displacement and no complications, so that the inclusion of additional radiographs during management or after cast removal would have had no added benefit. These results support previous studies indicating that forearm torus fractures in children may be safely treated using a wrist splint that can be removed at home by the parents [12][13][14].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, evidence from this research combined with the advantages of the splint support the use of this device in the treatment of these fractures. The use of splinting instead of casting has been previously established for buckle fractures of the distal radius in children [13][14][15][16] and Colles fractures in adults. 11,12 Our results contribute to the growing body of evidence that splinting is a suitable alternative to casting for specific fractures of the distal radius.…”
Section: Discussionmentioning
confidence: 99%
“…This modified scale has been used in another trial assessing wrist function after fracture. 15 The scale has been found to be highly reliable, 19,20 have excellent construct validity and be responsive to change. [17][18][19][20] It has been validated in populations of children 5 to 15 years old with fractures and other musculoskeletal problems.…”
Section: Outcome Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…1 Despite their high frequency, these fractures represent very stable injuries with excellent prognosis. 2 As a result, extensive evidence recommends their treatment with a removable wrist splint, rather than the traditional use of casting. [2][3][4][5][6][7][8] After the initial diagnosis and treatment, most of these fractures are managed by orthopedic surgeons.…”
mentioning
confidence: 99%